Influence of Constraining Barrier on the 5th Lumbar and 1st Sacral joint Compressive Force during Manual Lifting - I. Budihardjo; T. R. Derrick (Journal of Engineering and Technological Sciences, 2004)
The purpose of this study was to examine the mechanical stresses on the lower back as the response of different heights of constraining barrier. Ten male subjects lifted a load from the floor to the knuckle height under the non-constrained and the constrained conditions with 4 different heights of constraining barrier (80%, 100%, 120% and 140% of knee height). The constrained condition was defined as the condition where a load was placed on the floor behind a certain level of bar. When lifting of the constrained conditions, subjects significantly increased the peak compressive forces at L5/S1 compared to the non-constrained (3868.8 ± 527.5 N, 4175.0 ± 486.0 N, 4162.4 ± 462.3 N, 4136.0 ± 553.1 N, 4079.4 ± 468.9 N for 0%, 80%, 100%, 120% and 140% barrier height conditions respectively). The subjects moved the load further from L5/S1 in the horizontal direction when lifting during the constrained conditions. While lifting during the constrained conditions subjects generated an increase in the sacral angle and a decrease of the knee flexion. The peak compressive forces at L5/S1 showed a statistically significant quadratic trend. However, the magnitude of the difference of peak compressive forces during the constrained conditions was small.